Pediatric sequential organ failure assessment for predicting outcomes in ECMO-bridged pediatric heart transplant recipients: experience from the largest pediatric heart transplant center in China - Wang-zi Li; Xian-ming Zhou; Wei Su; Cheng Zhou; Guo-hua Wang; Jia-wei Shi; Nian-guo Dong (Frontiers in Medicine)
ObjectiveAdvanced heart failure in children sometimes requires mechanical circulatory support as a bridge to transplantation, with extracorporeal membrane oxygenation (ECMO) remaining a critical option despite its associated risks. The pediatric Sequential Organ Failure Assessment (pSOFA) may have potential in evaluating prognosis in ECMO-bridged candidates.Methods188 Children underwent orthotopic heart transplantation in Union hospital, Tongji Medical College, Huazhong University of Science and Technology, between January 2018 and April 2025 were studied retrospectively, with 24 received ECMO assistance as a bridge to transplant. Patients were divided into two groups according to outcomes while discharged. Serial pediatric Sequential Organ Failure Assessment and other medical data during bridging were collected for comparison.Results66.7% of the 24 patients survived to discharge, with mortality linked to younger age (p = 0.034), higher pre-ECMO pSOFA scores (p = 0.019), and congenital heart disease. ECMO cannulation was mostly peripheral (66.7%), with left heart decompression in 87.5%. External cardiopulmonary resuscitation (50% of cases) increased mortality risk (p = 0.027). The death group had higher peak/trough/average pSOFA scores, reinforcing its predictive value. Non-survivors had more complications (ECMO reuse, septic shock, neurological issues) after heart transplant. pSOFA trends distinguished outcomes: survivors showed declining scores (p = 0.006), and average pSOFA ≤8 predicted better survival (p = 0.003). ECPR patients had worse baselines but might recover with optimized management. Findings support pSOFA-guided risk stratification in ECMO-bridged HTx.ConclusionContinuous pSOFA monitoring effectively risk-stratifies ECMO-bridged pediatric transplant candidates, identifying high-risk patients after transplant. Planned ECMO initiation yields better outcomes than ECPR. These findings warrant prospective validation to optimize bridging strategies.